Overcoming dormancy of umbuzeiro seeds as a function of age and different concentrations of gibberellic acid (Research, Society and Development, 2022)
The overcoming of seed dormancy of umbuzeiro is important to enable the production of seedlings on a large scale, aiming the rehabilitation of areas in its natural habitat and the formation of commercial orchards, considering the economic potential of this native species of northeastern Brazil. The present work aimed to study the effect of storage and different concentrations of gibberellic acid (GA3) in overcoming dormancy in umbuzeiro seeds. The experiments were conducted in laboratory and vegetation house at the State University of Goiás, Ipameri University Unit, starting in August 2018. The experimental design used for the laboratory experiments was entirely randomized, with plots of 50 seeds, while in the vegetation house was randomized block design, with plots of 32 seeds. The treatments were arranged in a 2 x 5 factorial, consisting of seeds from two crops 2017 and 2018, and five GA3 concentrations (0, 250, 500, 750 and 1000 mg L-1). The final germination percentage, germination speed index and mean germination time, moisture content and electrical conductivity of the seeds under laboratory conditions were evaluated. In the greenhouse, the final germination percentage, germination speed index and mean germination time were evaluated. The relative water content of freshly harvested seeds obtained a higher average. On the other hand, the electrical conductivity did not differ statistically in relation to the different storage times of the umbuzeiro seeds. Newly harvested seeds performed better than stored seeds, while the concentration of 1000 mg L-1 of GA3 stood out in overcoming dormancy of umbuzeiro seeds.